Modern solutions in teaching English - Muminov Dilshod Abdurashidovich (Zien Journals, 2024)
In today's globalized world, proficiency in English is increasingly essential. This article delves into modern solutions for teaching English, emphasizing innovative methods, technological integration, and interactive approaches. Through a literature analysis, various methodologies are explored, followed by a discussion on their effectiveness. The results showcase promising outcomes, leading to conclusions and suggestions for optimizing English language education in the contemporary landscape
Keywords: English language education; modern solutions; innovative methods